Implementation of Active Deep Learner Experience (Adlx) Introflex to Improve Independent Learning in Elementary School Students - Paisah Paisah; Tri Murtini; Sri Sumartiningsih; Tri Joko Raharjo (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Strengthening independent learning at the elementary school level has become a strategic priority in 21st-century learning, amid increasing demands for critical, collaborative, and reflective thinking skills. However, independent learning among elementary school students is often considered underdeveloped due to their age and dependence on teacher guidance. This study aims to analyze in depth how the application of the ADLX-Introflex approach facilitates the growth of student learning independence at the Integrated Islamic Elementary School (SDIT). The study uses a phenomenological qualitative approach, with data collected through participatory observation, in-depth interviews, and learning documentation. Thematic and cross-case analyses were conducted to trace the gradual shift in learning regulation patterns throughout the learning cycle. This analysis was conducted to reveal the structure of students’ learning experiences during the implementation of ADLX-Introflex.  The results showed that the Active Deep Learner eXperience (ADLX)-based learning design, reinforced through the Introflex cycle, which includes individualization, interaction, observation, and reflection, shaped reflective, internalized learning independence. Students showed initiative in completing tasks, the ability to manage learning strategies contextually, and awareness of their learning processes and responsibilities. These findings challenge the assumption that independence in learning develops only at higher levels of education. Implicitly, the ADLX-Introflex approach can serve as a strategic pedagogical framework for building a foundation for long-term learning autonomy from elementary education onward.